Determinan Perilaku Merokok Pengunjung Kafe Di Kecamatan Lubuk Pakam - Safitri, Sintia; Siregar, Putra Apriadi (Preventia: The Indonesian Journal of Public Health, 2022)
Smoking is a habit that is widely practiced today by various groups. A total of 225,700 people died from smoking and other diseases caused by smoking in Indonesia. This study aims to determine the factors that most influence the smoking behavior of kafe visitors in Lubuk Pakam District. This research uses a combination research method (Mixed Method Research) with a Cross Sectional design. The data analysis technique used in this research is bivariate analysis. The results of this study indicate that there are 30 respondents (31.3 percent) who have smoking behavior and 66 respondents (68.8 percent) who do not have smoking behavior. Based on statistical tests, it was found that the variables related to the smoking behavior of the respondents were religious perspective on smoking law (p equal to 0.009), availability of cigarette ashtrays (p equal to 0.000), buying and selling cigarettes in kafes (p equal 0.000), family attitude (p equal 0.000) p equals 0.000), friends invite smoking (p equal 0.000), and cigarette advertisements (p equal 0.000). While the unrelated variables were religiosity (p equal to 0.160), smoker's family (p equal to 0.301) and the availability of air-conditioned rooms (p equal to 0.160). Based on the logistic regression test, it was found that the most influential variable on the smoking behavior of kafe visitors in Lubuk Pakam District was the availability of cigarette ashtrays at the kafe.